Orthodontic care and management in pregnant women - Sharma, Tanushree; Sharma, Aseem; Sharma, Akshat; Bansal, Chinki; Patyal, Arun (International Journal of Scientific Reports, 2022)
Orthodontic treatment is a lengthy procedure and it requires lots of care towards oral hygiene. Pregnancy brings lot of physiologic changes in patient. Proper management during gestational phase will provide better results. Orthodontist should have proper knowledge about the changes and should plan the treatment accordingly to achieve best outcome. The present article highlights the changes and the essential knowledge of various factors that an orthodontist should take into consideration while treating pregnant patients. This article also focuses on the treatment objectives that should avoid during pregnancy phase and explains the role of the patient during the treatment procedure.